A Critical Evaluation of Water Safety Plans (WSPs) and HACCP Implementation in Water Utilities - Dionysios S. Tsoukalas; Stavroula Tsitsifli (Proceedings, 2018)
The use of traditional risk management systems has proven to be insufficient to safeguard the safety of drinking water. Nowadays, it is preferable to apply preventive instead of corrective systems. Two of the most commonly used systems are the Hazard Assessment and Critical Control Points (HACCP) and the Water Safety Plans (WSPs). The major benefit of their implementation is the improvement of drinking water quality. Of course, the successful implementation of HACCP and WSPs in water utilities can be limited by a number of factors such as the lack of financial resources. However, the importance of implementation’s difficulties is minimal in relation to the benefits that may result from the application of HACCP and WSPs in water utilities.